Obstetric Intensive Care Admissions: 10-Year Review in a Portuguese Tertiary Care Centre - Vicente,Ana Patrícia (2021)
Abstract Overview and Aims: Maternal mortality has significantly decreased in past decades, especially in developed countries, where maternal morbidity became a main topic of research. Admission to an Intensive Care Unit (ICU) is considered an objective marker of severe maternal morbidity (SMM). Better knowledge of these patients is vital to achieve further maternal health improvements. This study aims to review obstetric ICU admissions. Study Design, Population and Methods: Retrospective transversal analysis of all obstetric ICU admissions between 2010 and 2019, in a tertiary care centre. Results: Thirty-eight women required obstetric ICU admission (1,59 for 1000 deliveries, 1,07% of all ICU admissions). Mean maternal age was 32 years, 57,9% were nulliparous, 34,2% were non-caucasian and 21,1% did not live in Portugal. Caesarean section was the main mode of delivery (86,8%), with 52,6% prematurity rate. The majority of ICU admissions were postpartum (97,4%), and median length of ICU stay was 3 days. Major obstetric haemorrhage (MOH) (44,7%) and hypertensive disorders (21,1%) were the most common diagnostics. The main interventions required were blood transfusion (57,9%) and mechanical ventilation (52,9%). No maternal deaths were recorded. Postpartum hysterectomy was performed in 5 patients (29,4% of MOH cases). Conclusions: Maternal morbidity and mortality analysis is vital, regarding maternal health care improvement. Few obstetric patients required ICU admission, with good outcomes. MOH and hypertensive disorders are the main causes for obstetric ICU admission. An increased number of non-caucasian and non-resident women can have some impact on ICU admission trends. Nonetheless, critically ill patients can be successfully managed with a multidisciplinary approach.